Analisis Yuridis Putusan Bebas terhadap Kasus Tindak Pidana Pembunuhan - Ramot Lumbantoruan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
The purpose of this research is to describe the legal arrangements regarding the Free Verdict according to positive legal provisions, the Judicial role of the Judge in deciding a case and Juridical Analysis of a conviction for a murder crime (Study of Judgment Number 423 / Pid / 2008 PN. South Jakarta. This research method is normative juridical research.The nature of this research is descriptive analysis, which is a method used to describe a condition or condition that is happening or ongoing in order to provide as much data as possible about the object of research so as to explore things that are ideal, then analyzed based on legal theory or applicable laws and regulations.Results of this study, first, the legal arrangements regarding the acquittal according to positive legal provisions is to look at Article 191 Paragraph (1), paragraph (2) and paragraph (3) of the Criminal Procedure Code specifically also provides an understanding that reinforces its role law about being free from all lawsuits. Second, the role of judges legally in deciding a case in the decision of Case Decision Number 423 / Pid / 2008 / PN. South Jakarta is a judge must pay attention to the interests of various parties, both the interests of the defendant, witnesses, and the interests of the Public Prosecutor.